Moderasi Beragama - Zam-Zami, Muhammad Abdul Basit (Indonesia Center for Middle East Studies, 2025)
Religious moderation is one of Majelis Hukama al-Muslimin’s agenda that aimed to creating a peaceful and tolerant society that upholds moral values and humanity, particularly among Muslims. This agenda has received support from the United Arab Emirates, because this moderation, besides being an ideal standard in religion practices, is also a necessity for the United Arab Emirates in realizing its various national interests. Based on these arguments, this research seeks to further explore the discourse of religious moderation that have become the agenda of Majelis Hukama al-Muslimin and United Arab Emirates in international community. This research is a descriptive qualitative study using library research methods. Through post-structuralism theory, this research observes that the Majelis Hukama al-Muslimin and the United Arab Emirates, through the discourse of religious moderation, have succeeded in forming a regime of truth by making moderate Islam the legitimacy of Islamic teachings. This has implications for religious moderation becoming a truth acknowledged by the global community. However, on the other hand, the success of this regime in voicing Islamic moderation has led to a decline in the influence of several other Islamic groups and organizations in the international community.